Sexual Behavior and Rights in Indonesian Prisons: A Qualitative Study Based on the Theory of Planned Behavior - Nendy Putra Salsabilla; Galuh Mega Kurnia; Rama Fatahillah Yulianto; Aprilia Nurhayati; Dewi Rokhmah; Iken Nafikadini (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
ntroduction: This study aimed to explore the policies and institutional factors influencing the fulfillment of prisoners’ sexual needs in Indonesia, particularly within the context of correctional health. With overcrowding in Indonesian prisons reaching as high as 370%, such as in the Class IIA Jember Penitentiary, and the lack of clear regulations addressing sexual rights, the objective was to examine behavioral drivers and systemic gaps using the Theory of Planned Behavior (TPB) framework to address unmet needs and prevent deviant sexual behavior. The TPB guided a deductive thematic analysis. Attitudes were operationalized as participants’ beliefs about outcomes, subjective norms as perceived social approval or pressure, and perceived behavioral control as perceived capacity/resources to enact or resist sexual behavior. Methods: This exploratory qualitative study was conducted at the Class IIA Jember Correctional Facility in 2022. A total of 15 informants were recruited using a snowball sampling technique, including the Head of the Correctional Facility, prison officers, health workers, and inmates. Data were collected through semi-structured interviews and analyzed thematically with deductive approach. Transcripts underwent verbatim transcription, TPB-focused line-by-line coding, coding matrices, and credibility checks (independent double-coding and member validation).Ethical approval was obtained from 173/KEPK/FKM-UNEJ/IV/2022 and both verbal and written informed consent were secured from all participants. Results: The primary findings indicated that subjective norms and perceived behavioral control significantly influenced prisoners' intentions to engage in risky sexual behavior. Contributing factors included ambiguous regulations on sexual health education and inmate guidance, the suboptimal implementation of assimilation and reintegration policies, and the absence of a formal conjugal visit program. These regulatory shortcomings may increase the risk of sexually transmitted disease transmission within the prison environment. Conclusion: This study contributes to the understanding of sexual health policy implementation within Indonesian correctional institutions by identifying key regulatory and systemic deficiencies. It offers critical insights into how institutional support, or its absence, influences inmates’ health-related behaviors. Future research should focus on developing and implementing policies that safeguard prisoners’ sexual health rights, thereby advancing knowledge in the fields of correctional health and human rights.